FRI0369 Pattern of Clinical Presentation and Disease Severity in Patients with Polymyalgia Rheumatica. (15th July 2016) - Camellino, D.; Sobrero, A.; Tomatis, V.; Paolino, S.; Cutolo, M.; Cimmino, M.A.
Abstract : Background: Polymyalgia rheumatica (PMR) is an inflammatory disorder of the elderly characterized by girdle pain and stiffness, constitutional symptoms and elevation of inflammatory indexes. In its classical form, the shoulder girdle is affected, associated or not with pelvic and spinal pain. The latter two locations can occasionally precede shoulder involvement. It is not known if the pattern of clinical presentation is related to disease severity at onset. Objectives: In this study, disease severity of PMR has been correlated with clinical characteristics at presentation. Methods: 394 patients (251 women, median age 73 yrs, range 47–92 yrs) with PMR diagnosed according to Bird's criteria, visited between 1990 and 2014 by the same clinician were studied. Clinical features recorded at disease presentation included initial involvement of: i) the shoulder girdle; ii) the pelvic girdle; iii) the column; iv) two or more of the previous locations; v) presence of giant cell arteritis (GCA); vi) acute onset, defined as completion of full symptoms and signs in ≤72h; or vii) peripheral arthritis. Disease severity of PMR was evaluated by considering: i) weight loss; ii) fever; iii) morning stiffness (MS); iv) ESR; v) CRP; and vi) initial dose of prednisone. Results: Acute onset and classical involvement of the shoulder girdle were not associated with our indicators of PMR severity. By contrast, onset in the pelvic girdle (p=0.002), simultaneous onset in multiple locations (p=0.006), peripheral arthritis (p=0.045) and GCA (p=0.0004) were associated with a higher initial dose of prednisone; multiple locations onset correlated also with MS (p=0.044). Conclusions: The presentation with multiple locations, including column and pelvic girdle, peripheral arthritis, and GCA resulted in a more severe onset at least in the perception of the clinician who used a higher initial dose of prednisone. Clinicians should consider the pattern of disease presentation when evaluating the burden of PMR. Disclosure of Interest: None declared